Race affects SVR12 in a large and ethnically diverse hepatitis C‐infected patient population following treatment with direct‐acting antivirals: Analysis of a single‐center Department of Veterans Affairs cohort. Issue 2 (22nd February 2018) - Benhammou, Jihane N.; Dong, Tien S.; May, Folasade P.; Kawamoto, Jenna; Dixit, Ram; Jackson, Samuel; Dixit, Vivek; Bhattacharya, Debika; Han, Steven B.; Pisegna, Joseph R.
Abstract: Hepatitis C virus (HCV) infection is a major cause of chronic liver disease. HCV cure has been linked to improved patient outcomes. In the era of direct‐acting antivirals (DAAs), HCV cure has become the goal, as defined by sustained virological response 12 weeks (SVR12) after completion of therapy. Historically, African‐Americans have had lower SVR12 rates compared to White people in the interferon era, which had been attributed to the high prevalence of non‐CC interleukin 28B (IL28B) type. Less is known about the association between race/ethnicity and SVR12 in DAA‐treated era. The aim of the study is to evaluate the predictors of SVR12 in a diverse, single‐center Veterans Affairs population. We conducted a retrospective study of patients undergoing HCV therapy with DAAs from 2014 to 2016 at the VA Greater Los Angeles Healthcare System. We performed a multivariable logistic regression analysis to determine predictors of SVR12, adjusting for age, HCV genotype, DAA regimen and duration, human immunodeficiency virus (HIV) status, fibrosis, nonalcoholic fatty liver disease (NAFLD) fibrosis score, homelessness, mental health, and adherence. Our cohort included 1068 patients, out of which 401 (37.5%) were White people and 400 (37.5%) were African‐American. Genotype 1 was the most common genotype (83.9%, N = 896). In the adjusted models, race/ethnicity and the presence of fibrosis were statistically significant predictors of non‐SVR. African‐Americans had 57% lower odds for reaching SVR12 (adj.OR = 0.43, 95% CI = 1.5‐4.1) compared to White people. Advanced fibrosis (adj.OR = 0.40, 95% CI = 0.26‐0.68) was also a significant predictor of non‐SVR. In a single‐center VA population on DAAs, African‐Americans were less likely than White people to reach SVR12 when adjusting for covariates.